Ceropegia tribounii (Apocynaceae, Asclepiadoideae), a new species from western Thailand - Kidyoo, Manit (Phytotaxa, 2015)
Ceropegia tribounii Kidyoo (Apocynaceae, Asclepiadoideae), a recently discovered, endangered species from western Thailand, is described as new. Comprehensive descriptions, illustrations, photographs, and diagnostic comparisons with morphologically similar species, such as C. anjanerica, are provided here. Ceropegia tribounii can be easily recognized by its sessile, linear leaves and its broadly obovate corolla lobes that are shorter than the corolla tube, as well as by its interstaminal corona with a pilose inner surface.